Hand Eye Coordination and Explosive Power of Limb Muscles for Under Ring Ability in playing Basketball - Ibnu Andli Marta; Hendri Neldi (Universitas PGRI Palembang, 2023)
The problem in this study is the under ring shooting ability possessed by the extracurricular basketball participants of SMAN 2 Tebo which is still low. This study aims to see the relationship between eye-hand coordination and explosive power of leg muscles to the ability to shoot under the basketball hoop. This type of research is correlational with two free variables. the sample in this study was all participants in basketball extracurricular activities totaling 34 people. The instruments used are vertical jump, tennis ball catch throw and shooting under ring. The data in this study were analyzed using simple correlation and double correlation. The results are as follows: (1) There is a relationship of eye-hand coordination to the shooting under ring ability of basketball players with a calculated r value of 0.439 > rtable 0.344, (2) There is a relationship of the explosive power of the leg muscles to the shooting ability of the under hoop of basketball players with a calculated r value of 0.402 > rtable 0.344, (3) There is a relationship between eye-hand coordination and explosive power of limb muscles simultaneously to the shooting under hoop ability of basketball players with a calculated rvalue of 0.518 > rtable 0.344 and with acalculated F value of 5.69 > Ftable 3.30.